You certainly are missing a step. Let the growth rate r=1.037
Year 1: p1 = 30000
year 2: p2 = p1 * 1.037 = 30000 * 1.037 = 3110
year 3: p3 = p2 * 1.037 = 31110 * 1.037 = 32261
Nite that p2 = p1*r
p3 = p2*r = p1 * r^2
see a pattern here? No, go back to your text.
pn = p1 * r^(n-1)
Now you should be able to get p6
A city has a population of 30,000 people. Suppose that each year the population grows by 3.7% . What will the population be after 6 years?
i multiplied 30,000 by 6 then 3.7 and got 7425000 i don't think that's the answer i feel like im missing a step..
1 answer